2017
DOI: 10.3389/fmicb.2017.00460
|View full text |Cite
|
Sign up to set email alerts
|

Morin Attenuates Streptococcus suis Pathogenicity in Mice by Neutralizing Suilysin Activity

Abstract: Streptococcus suis, a Gram-positive pathogen, is widely recognized as an important agent of swine infection, and it is also known to cause a variety of zoonoses, such as meningitis, polyarthritis and pneumonia. Suilysin (SLY), an extracellular pore-forming toxin that belongs to the cholesterol-dependent cytolysin family, is an essential virulence factor of S. suis capsular type 2 (SS2). Here, we found that morin hydrate (morin), a natural flavonoid that lacks anti-SS2 activity, inhibits the hemolytic activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…As shown in Fig. 1C, the supernatants from SS2 culture medium showed hemolysis activity, as previously reported (27). The supernatants from an SS2 and amentoflavone (8 to 32 g/ml) coculture system showed significantly lower hemolysis activity than that from SS2, suggesting that amentoflavone attenuated the hemolytic activity of SS2 culture supernatants.…”
Section: Resultssupporting
confidence: 86%
“…As shown in Fig. 1C, the supernatants from SS2 culture medium showed hemolysis activity, as previously reported (27). The supernatants from an SS2 and amentoflavone (8 to 32 g/ml) coculture system showed significantly lower hemolysis activity than that from SS2, suggesting that amentoflavone attenuated the hemolytic activity of SS2 culture supernatants.…”
Section: Resultssupporting
confidence: 86%
“…Recently, several studies have reported that flavonoids including myricetin and morin hydrate can significantly weaken the virulence of SS2, and furthermore, the weakened pathogenicity of bacteria is due to the inhibition of hemolytic activity of suilysin ( Li et al, 2017 ; Niu et al, 2017 ). Fisetin also belonging to flavonoids, as a potential antimicrobial compound, has been identified ( Taechowisan et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies aimed at discovering novel potent inhibitors of SLY and additional research to confirm the mechanism of interaction between SLY and its inhibitors are essential. In our previous literature, it was reported that morin, a natural compound could inhibit the haemolytic activity of SLY by restraining the transformation from the monomer form to the oligomer form based on the binding direct to the domain 2 of SLY 21 . In the present study, we observed that the natural compound myricetin (MYR) could inhibit the haemolytic activity of SLY.…”
Section: Introductionmentioning
confidence: 99%